From Cheap to Charming: Rejuvenating Low-Cost Brands - Åström,Anna; Hammarlund,Frida; Hassel,Rebecka (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose This paper aims to explore how low-cost brands can rejuvenate and create an emotionally engaging brand identity, moving beyond their low-price positioning. Methodology A qualitative research approach has been used, drawing on both primary and secondary data. The primary data consist of semi-structured interviews exploring low-cost brands and their marketing. The secondary data includes a dual case study of two low-cost brands, Lidl and Eldorado, supported by a literature review of relevant theoretical concepts. Findings This study explores how low-cost brands can rejuvenate and create emotionally engaging identities beyond their low-cost positioning. The analysis shows that humor and irony serve as key tools for transforming functional associations into emotional connections. Lidl and Eldorado both used these strategies to turn the stigma of low-cost consumption into positive social commentary and brand personality. While both generated cultural buzz and a favorable halo effect, Eldorado achieved a more coherent rejuvenation. To support managers in similar efforts, we propose a checklist emphasizing four consistency pillars: Identity, Relevance, Alignment, and Impact.
Keywords: Brand identity; Revitalization; Rejuvenation; Low-cost brands; Humor; Irony; Brand extension